Child Labor 14

Algebra Level 4

{ 1 a 2 + 1 a b + 1 b 2 = 3 1 b 2 + 1 b c + 1 c 2 = 1 1 c 2 + 1 c a + 1 a 2 = 2 \begin{cases} \dfrac{1}{a^2} + \dfrac{1}{ab} + \dfrac{1}{b^2} = 3 \\ \dfrac{1}{b^2} + \dfrac{1}{bc} + \dfrac{1}{c^2} = 1 \\ \dfrac{1}{c^2} + \dfrac{1}{ca} + \dfrac{1}{a^2} = 2 \end{cases}

Given that a , b a,b and c c satisfy the system of equations above, then a , b a,b and c c follows a/an:

Harmonic Progression Geometric Progression Arithmetic Progression None of these choices

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Rajen Kapur
Oct 21, 2015

Multiply the first equation by ( 1 a 1 b ) (\dfrac{1}{a} - \dfrac{1}{b}) to get ( 1 a 3 1 b 3 ) = ( 3 a 3 b ) (\dfrac{1}{a^3} - \dfrac{1}{b^3}) =( \dfrac {3}{a} - \dfrac{3}{b}) . Similarly, the next two by ( 1 b 1 c ) (\dfrac{1}{b} - \dfrac{1}{c}) and ( 1 c 1 a ) (\dfrac{1}{c} - \dfrac{1}{a}) , respectively. Adding all the three equations, 0 = ( 3 a 3 b ) + ( 1 b 1 c ) + ( 2 c 2 a ) 0 = (\dfrac {3}{a} - \dfrac{3}{b}) +( \dfrac {1}{b} - \dfrac{1}{c})+ ( \dfrac {2}{c} - \dfrac{2}{a}) which simplifies to 1 a + 1 c = 2 b \dfrac {1}{a} + \dfrac{1}{c} = \dfrac {2}{b} . Hence a, b, c are in H.P.

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...